Reliability and validity of the Turkish version of the Physical Activity Questionnaire for Older Children (PAQ-C) - ERGÜN, AYŞE (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2019)
Background/aim: The Physical Activity Questionnaire for Older Children (PAQ-C) is one of the most frequently used questionnaires for evaluating moderate to vigorous levels of physical activity in children. However, a Turkish version of the questionnaire was not available. This study aimed to create a Turkish version of the PAQ-C and examine its psychometric characteristics and factor structure. Materials and methods: The study was conducted with 784 primary school students (ages 9-14 years). The PAQ-C was examined for content and construct validity and analyzed in terms of reliability. Content validity was evaluated with the content validity index (CVI), construct validity, exploratory factor analysis (EFA) (n 388), and confirmatory factor analysis (CPA) (n = 396). For reliability analysis, Cronbach's alpha and the intraclass correlation coefficient (ICC) were calculated. The factor construct was assessed with corrected item total correlations (CITCs). Results: The CVI for the PAQ-C was 0.95. EFA revealed a two-factor construct of 'at school' and 'extracurricular'. CFA confirmed the two-factor construct. Factor loadings varied between 0.41 and 0.80. Cronbach's alpha was 0.77 and ICC was 0.91 for the test-retest for the entire sample. All CITCs were >0.20. Conclusion: The PAQ-C is a valid and reliable instrument that can be used for Turkish children.
Keywords: Child; exercise; psychometrics; schools; students; surveys and questionnaires; VALIDATION